Peak-To-Peak Average Power Ratio Reduction In Orthogonal Frequency Division Multiplexing System Using The Combination Of Comapnding And Pre-Coding Techniques - Ooi, Xin Kai (Universiti Sains Malaysia, 2017)
An orthogonal Frequency Division Multiplexing (OFDM) system has been widely used in the field of wireless communication application. However, there is a major drawback for OFDM systems which is high Peak to Average Power Ratio (PAPR). PAPR is one of the most important problems in OFDM when the independent phase of the subcarrier will often combine constructively. High PAPR reduces the system efficiency and increases the system complexity. In this project, the main technique used to reduce the high PAPR in OFDM system are μ-law companding and exponential companding. The algorithm of the both techniques will be introduced. Pre-coding technique will be investigated to combine with the algorithm of the μ-law companding and exponential companding to improve the PAPR reduction. DCT μ- law companding, FWHT μ-law companding, DCT exponential companding and FWHT exponential companding have been designed to reduce the problem of high PAPR. The proposed combined techniques had been simulated by Matlab software to investigate the result about the reduction of PAPR and Bit Error Ratio (BER). For the performance of PAPR reduction about the proposed combined techniques, the best technique is DCT μ-Law Companding Technique due to its highest improvement in PAPR, which is 2.044 (31.16%) with modulation of QPSK at N = 64. For the performance of BER, the BER of the DCT μ- law companding technique (0.2288) and FWHT μ-Law companding technique (0.2357) is significantly higher than exponential techniques.